People expectations regarding multinational corporation’s impacts towards host country / Nur Hidayah @ Hidayu Md Norani and Noorhaslinnda Ali - Md Norani, Nur Hidayah @ Hidayu; Ali, Noorhaslinnda (Faculty of Business and Management, 2014)
This study is focusing on the people expectations regarding what positive impacts that Multinational Corporation (MNC) had brought to the host countries. The definition of Multinational Corporation (MNC) is any company that engages in business functions beyond its domestic border, (John B. Cullen 2010). The impacts have potential to affect the host countries economic activities. The main objective of this project paper is to determine whether there is a knowledge sharing, technological development and creation of employment opportunities in the host countries through Multinational Corporation’s activities. The research is focusing on the positive impacts of Multinational Corporation. The theoretical framework of this study consists of dependent variable and independent variables. The sample size of this study was 100 respondents from International Business students at Universiti Teknologi Mara (UiTM). Data was obtained by using primary and secondary data. Respondents were required to answer the questionnaires that included the statements of each variable. Once the necessary data was collected, the data was analyzed and summarized in a readable and easily interpret form. The Statistical Package for the Social science (SPSS) version 21.0 was used to summarize the data. The results are in the form of frequency distribution, correlation coefficient, reliability testing, descriptive statistic and regression analysis.